Publishing during a Pandemic: Analyzing Recent Publication Times in Hand Surgery - Ann Carol Braswell, BS; Anthony Wilson, MD; Gabrielle Willhelm, MD; Mohamed Morsy, MD; Rachel E. Aliotta, MD (Plastic and Reconstructive Surgery, Global Open)
Background:. Timely distribution of research is crucial for improving treatments and patient care; however, the publication process is historically unhurried. The primary goal of this study was to analyze the time to publication in hand surgery for 5 years and to examine potential factors affecting publication speed. Methods:. A 5-year review (2017–2021) was performed on 4 major hand surgery journals. The Journal of Hand Surgery American Volume, Journal of Hand Surgery European Volume, Journal of Plastic Surgery and Hand Surgery, and Plastic and Reconstructive Surgery were included in the review. Differences were assessed using analysis of variance or 2-sided independent t tests for continuous variables. Results:. There was a significant difference in submission-to-publication time between journals (P < 0.001). This differed by year (P < 0.001), with a significant increase in time from submission to publication after 2019, during the COVID-19 pandemic (447 ± 198 versus 406 ± 169 d, P < 0.001). Geographic region of the primary institution did affect submission-to-publication time (P < 0.001). No significant difference was seen in submission-to-publication time based on the number of institutions contributing, article type, or first author or corresponding author surgical specialty (P > 0.05). Conclusions:. Time to publication in hand surgery varies by hand surgery journal and significantly increased during the COVID-19 pandemic. New research reflects work done over a year ago at least. Participation in the peer-review process should be encouraged and bolstered within the hand surgery community to improve research dissemination times within the field.